2010
DOI: 10.1021/jo100915e
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Acid Induced Mukaiyama Aldol Type Reaction of Sterically Hindered Ketones

Abstract: 1,1,3,3-Tetrakis(trifluoromethanesulfonyl)propane (Tf(2)CHCH(2)CHTf(2)) is one of the most effective Brønsted acid precatalysts for the Mukaiyama aldol type reactions of sterically hindered ketones. By using Tf(2)CHCH(2)CHTf(2) in a range from 0.5 to 2.0 mol %, the vinylogous Mukaiyama aldol reaction of alpha-substituted cyclohexanones with 2-silyloxyfurans smoothly proceeded to give the aldol products in excellent yield without the loss of diastereoselectivity. Under similar conditions, acyclic ketene silyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 44 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…In this review, we have showed that much excellent progress has been made in the development of the homogeneous catalytic aldol reaction, which offer many valuable synthetic tools to construct new carbon-carbon bond and make complex or chiral carbonyl compounds directly. It is no problem that the invention of a novel type of homogeneous catalysts in the aldol reaction is a competitive and attractive research field (320)(321)(322)(323)(324)(325). Moreover, the studies with versatile substrates inspired from simple aldehydes or ketones have shown that aldol reaction is a powerful process to prepare desired molecules (326)(327)(328)(329)(330)(331).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we have showed that much excellent progress has been made in the development of the homogeneous catalytic aldol reaction, which offer many valuable synthetic tools to construct new carbon-carbon bond and make complex or chiral carbonyl compounds directly. It is no problem that the invention of a novel type of homogeneous catalysts in the aldol reaction is a competitive and attractive research field (320)(321)(322)(323)(324)(325). Moreover, the studies with versatile substrates inspired from simple aldehydes or ketones have shown that aldol reaction is a powerful process to prepare desired molecules (326)(327)(328)(329)(330)(331).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, Tf 2 CHCH 2 CHTf 2 (3)w as found to be one of the most effectivea cids (entry 1). [28] b-Branched acid 23 also acted as af ormal catalyst (entry 2). [29] On the other hand, despite the absence of any acidic moieties, 2-fluoropyridinium compound 4f efficientlyp romoted the reaction (entries 3a nd 4), whereas nonhalogenated pyridinium compound 4a proved less fruitful (entry 5).…”
Section: Formalcatalysis By 2-fluoropyridiniummentioning
confidence: 99%
“…The notable catalysis of Tf 2 CHCH 2 CHTf 2 3 was observed not only in the VMM reaction but also in the Mukaiyama aldol reaction. 28) Rhodes pointed out that the reaction of sterically bulky undecan-6-one 8a with a ketene silyl acetal did not yield the corresponding aldol product under classical titanium tetrachloride (TiCl 4 )-mediated conditions 29) (Chart 8). On the other hand, only 1.0 mol% of 3 was sufficient to complete this reaction, giving rise to 9.…”
Section: Hikaru Yanaimentioning
confidence: 99%